The Lebanese COVID-19 Cohort; A Challenge for the ABO Blood Group System - Khalil, Athar; Feghali, Rita; Hassoun, Mahmoud (Frontiers in Medicine, 2020)
A sudden outbreak of pneumonia caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has rapidly spread all over the world facilitating the declaration of the resultant disease as a pandemic in March,2020. In Lebanon, the fast action of announcing a state of emergency with strict measures was among the factors that helped in achieving a successful containment of the disease in the country. Predisposing factors for acquiring COVID-19 and for developing a severe form of this disease were postulated to be related to epidemiological and clinical characteristics as well as the genomics signature of a given population or its environment. Biological markers such as the ABO blood group system was amongst those factors that were proposed to be linked to the variability in the disease course and/or the prevalence of this infection among different groups. We therefore conducted the first retrospective case-control study in the Middle-East and North Africa that tackles the association between the blood group types and the susceptibility as well as the severity of SARS-CoV2 infection. Opposing to the current acknowledged hypothesis, our results have challenged the association significance of this system with COVID-19. Herein, we highlighted the importance of studying larger cohorts using more rigorous approaches to diminish the potential confounding effect of some underlying comorbidities and genetic variants that are known to be associated with the ABO blood group system.